Why so few women?. - Applewhite, A.
Women account for only 15-20 percent of computer science majors in the United States, and the percentage has dropped over the last five years. By avoiding computers, women may be missing out on the generous salaries and abundant career opportunities in information technology. The paper considers this troubling trend
Keywords: United States; Career opportunities; Computer science education; Gender; Information technology; Salaries; Women